ZEBRA cell‐penetrating peptide as an efficient delivery system in Candida albicans. Issue 8 (12th February 2014) - Marchione, Roberta; Daydé, David; Lenormand, Jean‐Luc; Cornet, Muriel
Abstract There is increasing interest in drug delivery systems, such as nanoparticles, liposomes, and cell‐penetrating peptides, for the development of new antimicrobial treatments. In this study, we investigated the transduction capacity of a carrier peptide derived from the Epstein–Barr virus ZEBRA protein in the pathogenic fungus Candida albicans. ZEBRA‐minimal domain (MD) was able to cross the cell wall and cell membrane, delivering eGFP to the cytoplasm. Uptake into up to 70% of the cells was observed within two hours, without toxicity. This new delivery system could be used in C. albicans as a carrier for different biological molecules including peptides, proteins, and nucleic acids. Thereby, in antifungal therapy, MD may carry promising bioactive fungal inhibitors that otherwise penetrate poorly into the cells. Furthermore, MD will be of interest for deciphering molecular pathways involving cell‐cycle control in yeast or signaling pathways. Short interfering peptides could be internalized using MD, providing new tools for the inhibition of metabolic or signaling cascades essential for the growth and virulence of C. albicans, such as yeast‐to‐hyphae transition, cell wall remodeling, stress signaling and antifungal resistance. These findings create new possibilities for the internalization of cargo molecules, with applications for both treatment and functional analyses.